2007
DOI: 10.1200/jco.2007.11.9776
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Trastuzumab in Heavily Pretreated Metastatic Breast Cancer

Abstract: Capecitabine plus trastuzumab appears to be an effective and safe option in a heavily pretreated population. Therefore, a direct comparison of this regimen with capecitabine monotherapy in this setting is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 27 publications
3
70
1
3
Order By: Relevance
“…This was associated with a clinical benefit rate of 70%. In addition, the time to progression (TTP) of 8 months and overall survival duration of 24 months were much higher than those seen in historical controls of patients treated with capecitabine monotherapy [3]. A retrospective analysis of 136 patients with HER-2/neu ϩ breast cancer found that 66 and 47 patients received trastuzumab in the first and second line, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was associated with a clinical benefit rate of 70%. In addition, the time to progression (TTP) of 8 months and overall survival duration of 24 months were much higher than those seen in historical controls of patients treated with capecitabine monotherapy [3]. A retrospective analysis of 136 patients with HER-2/neu ϩ breast cancer found that 66 and 47 patients received trastuzumab in the first and second line, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior to the 2009 publication of a clinical trial showing a higher response rate and longer progression-free survival interval, there were no randomized data to support this practice. There were only data from uncontrolled studies [2,3] and case series [4 -7] suggesting that the practice was safe and not associated with excess toxicity. In addition, responses and longer survival were seen with subsequent lines of trastuzumabbased therapy; however, given the lack of randomization, several articles called for randomized trials to clarify the true benefit [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phase II studies investigating the efficacy and tolerability of trastuzumab in combination with paclitaxel have shown diarrhoea to be the most frequent toxicity manifesting in 30 % of patients [87]. Toxicity profiling for newer combination regimens where trastuzumab is given with carboplatin or capecitabine has shown significant induction of mucositis, diarrhoea and vomiting at grade 3-4 intensity [88,89].…”
Section: Targeted Anti-cancer Agents and Mucosal Injurymentioning
confidence: 99%
“…On the other hand, changing the traditional treatment paradigm in patients progressing on trastuzumab and administering further trastuzumab-based therapy beyond disease progression may have clinical benefit [65][66].This "treatment beyond progression" approach is increasingly being studied in clinical trials by combining trastuzumab either with chemotherapy [67][68] or with another targeted agent, such as the RTKI lapatinib [69]. Trastuzumab-DM1 (T-DM1) is an anti-HER-2 antibody drug conjugate comprising trastuzumab linked to the maytansine derivative DM1.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%